2015
DOI: 10.1128/aac.01151-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-1 Resistance to Tenofovir AlafenamideIn Vitro

Abstract: Tenofovir alafenamide (TAF) is an investigational prodrug of the HIV-1 nucleotide reverse transcriptase (RT) inhibitor (NtRTI) tenofovir (TFV), with improved potency and drug delivery properties over the current prodrug, tenofovir disoproxil fumarate (TDF). TAF is currently in phase 3 clinical studies for the treatment of HIV-1 infection, in combination with other antiretroviral agents. Phase 1 and 2 studies have shown that TAF was associated with increased peripheral blood mononuclear cell (PBMC) drug loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…We confirmed that HIV-1 Q151M also caused moderate-level resistance to AZT (~5-fold); the combination of Q151M and F116Y decreased AZT sensitivity further, as expected (IC 50 : 0.2 μM) (Table 2 ). Notably, mutations including Q151M and some accessory mutations are also reportedly cause intermediate-level resistance to 3TC and TDF 25 ; however, such resistance was not caused by any variants tested in this study (Table 2 ). Critically, EFdA activity against HIV-1 Q151M and HIV-1 Q151M/Y115F/F116Y increased (IC 50 : 30 pM for both variants) when compared to that against HIV-1 WT (IC 50 : 0.4 nM).…”
Section: Resultsmentioning
confidence: 66%
“…We confirmed that HIV-1 Q151M also caused moderate-level resistance to AZT (~5-fold); the combination of Q151M and F116Y decreased AZT sensitivity further, as expected (IC 50 : 0.2 μM) (Table 2 ). Notably, mutations including Q151M and some accessory mutations are also reportedly cause intermediate-level resistance to 3TC and TDF 25 ; however, such resistance was not caused by any variants tested in this study (Table 2 ). Critically, EFdA activity against HIV-1 Q151M and HIV-1 Q151M/Y115F/F116Y increased (IC 50 : 30 pM for both variants) when compared to that against HIV-1 WT (IC 50 : 0.4 nM).…”
Section: Resultsmentioning
confidence: 66%
“…Finally, the increase in TFV-DP levels may also lead to an improved resistance profile for TAF over TDF. In vitro, the resistance profile of TAF is similar to that of TDF/TFV (see our accompanying paper [27]). However, as previously demonstrated, the intracellular TFV-DP levels achieved with TAF were 5 times higher than those with TDF.…”
Section: Discussionmentioning
confidence: 89%
“…The panel agreed that TDF and TAF should receive similar mutation penalty scores but stipulated that this decision should be re-evaluated if the greater intracellular levels of tenofovir produced by TAF could be shown to be clinically significant in the presence of reduced in vitro tenofovir susceptibility [ 32 , 33 ]. In response to the panel’s recommendation to indicate which of the two DRV/r and DTG dosing schedules should be used, the HIVDB output was modified to include comments indicating that the higher dosing schedule should be used in the presence of low-level, intermediate, or high-level resistance to these ARVs [ 12 , 14 , 34 ].…”
Section: Discussionmentioning
confidence: 99%